PENGARUH PEMBIASAAN MENDENGARKAN LAGU ANAK TERHADAP PERKEMBANGAN BAHASA EKSPRESIF ANAK USIA 4-5 TAHUN - Intan Maharani Yusirianti; Ervin Nurul Affrida (STKIP Subang, 2026)
The development of expressive language is an important aspect in early childhood development because it plays a role in the ability to communicate and interact with the environment. However, there are still children aged 4–5 years who have difficulty expressing ideas, answering questions, and constructing simple sentences, so stimulation that is appropriate to the characteristics of child development is needed. This study aims to determine the effect of listening to children's songs on the expressive language development of 4–5-year-old children at Dharma Bhakti Kindergarten in Surabaya. This study uses a quantitative approach with a pre-experimental method through a one group pretest-posttest design. There were 14 children in the study. Data collection techniques were conducted through tests and observations. Data analysis used a t-test (paired sample t-test). The results showed a significant increase, with a pretest average score of 3.96 increasing to 5.28 in the posttest, and the t-value of 3.47 was greater than the critical t-value of 1.77 at a significance level of 0.05 Thus, the habit of listening to children's songs was proven to have an effect on the development of children's expressive language.